2001
DOI: 10.1016/s0307-904x(01)00020-8
|View full text |Cite
|
Sign up to set email alerts
|

A fifth generation numerical modelling system in coastal zone

Abstract: Nowadays, artificial intelligence (AI) technology is gradually integrated into the numerical modelling system to make the system more intelligent and more user-friendly. The characteristics of the fifth generation numerical modelling are connected with AI applications. The expert system technology as a widely applied AI technology, is integrated into our modelling system for coastal water processes with traditional numerical computational tools and the data and graphical pre-processing and post-processing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Details regarding the location map of the Shing Mun River and its tributary nullahs can be found in Chau and Lee (1991a,b) and Chau and Chen (2001). The main conveyance channel is of trapezoidal shape with side slope of 1 in 1.5 along most length.…”
Section: The Study Areamentioning
confidence: 99%
“…Details regarding the location map of the Shing Mun River and its tributary nullahs can be found in Chau and Lee (1991a,b) and Chau and Chen (2001). The main conveyance channel is of trapezoidal shape with side slope of 1 in 1.5 along most length.…”
Section: The Study Areamentioning
confidence: 99%
“…Ragas et al [11] suggested, though they did not actually implement, the development of an expert system for model selection in order to deal with uncertainty in model predictions, after compared a number of UK and USA models. Nowadays, the fifth generation modelling system [20,24,25] is acknowledged to have the features of integrating AI technology and computational hydrodynamics into a single system to furnish assistance for non-experienced user.…”
Section: Tendency In Modellingmentioning
confidence: 99%
“…After comparing a number of U.K. and U.S.A. models, Ragas et al [11] suggested, although they did not actually implement, the development of a KBS for model selection in order to deal with uncertainty in model predictions. The fifth generation of modeling system [17,25,26] is acknowledged to have the features to allow AI technology and computational hydrodynamics to be integrated into a single system to furnish assistance for non-experienced users.…”
Section: Knowledge-based Systems (Kbss)mentioning
confidence: 99%